The hidden nitrogen nexus: stochastic assembly and linear gene synergies drive urban park microbial networks - Li, Maoping; Bi, Jie; Wang, Xiaochen; Li, Huan (Frontiers in Microbiology, 2025)
Urban parks play a significant role in environmental greening, cultural heritage, and recreational activities. The diversity and distribution of park environmental microbiota have become a hot focus of microbial ecology. However, there has been limited attention on the functional attributes of microbial communities, highlighting the importance of studying the distribution and diversity of functional genes in urban parks. Here, we employed metagenomic sequencing and binning to explore the diversity, assembly, and functional synergy of nitrogen cycling genes from the grassland soil and water in urban parks. Our results showed that glutamate metabolism and assimilatory nitrate reduction are the predominant nitrogen cycling pathways in both the soil and water. The diversity of nitrogen cycling genes in water was more abundant than in soil. The assembly of nitrogen cycling genes in both the soil and water was primarily driven by stochastic processes. Nutrient factors (such as total sulfur) were the most significant influencers of nitrogen cycling genes in park soil, while bacterial communities were the most critical determinants in water. The gene narH, involved in multiple nitrogen cycling metabolic pathways, was identified as an important marker of nitrogen storage in both soil and water. Through metagenomic binning, we discovered linear arrangements of multiple nitrogen cycling genes, such as narG-narH-narJ-narI, which collectively participate in the reduction of nitrate to nitrite, demonstrating the synergy, functional redundancy, and complementarity among nitrogen cycling genes. Our study holds significant implications for the biochemical cycling and the management of nitrogen pollution in urban parks.